Unravelling giant molecular clouds - Liang, F (2024)
Giant molecular clouds (GMCs) provide the fuel for star formation and bear various feedbacks. Thus, they are key to our understanding of galaxy evolution and the baryon cycle. In this thesis, I study the cold molecular gas content in the nearby universe, including three megamaser-host galaxies, one early-type galaxy, and the central molecular zone (CMZ) of the Milky Way (MW). The spatial scales probed by the analyses range from kpc-scale gas discs (i.e. the environment GMCs reside in) to sub-pc clumps within GMCs.